Contact metamorphism of the Black Hawk Zn-Pb-Cu deposit, Hancock County, Maine - Yates, Martin; Howd, Frank (Atlantic Geology, 1988)
The Black Hawk Zn-Cu-Pb deposit is located along the northern margin of the Sedgwick pluton within metasedimentary and metavolcanic rocks of the Ellsworth Schist. Most of the ores are composed of strati graphically conformable, sphalerite-rich layers with locally high concentrations of galena, pyrite, pyrrhotite, and chalcopyriie. Galena-rich ores contain irregular intergrowths of tetrahedrite, boumonite, and boulangerite. The ore shows evidence of annealing and coarsening due to metamorphism. The boundary between the Ellsworth Schist and the Sedgwick pluton is irregular due to the large number of granitic dikes emanating from the pluton. The Ellsworth Schist is regionally metamorphosed to the greenschist facies, and in the contact aureole of the pluton in the Black Hawk deposit schists contain cordierite and anthophyllile. A Si-poor, Mg-rich unit contains enstatite and spinel porphyroblasts in a fine-grained, massive talc, chlorite, and phlogopite groundmass. Sulfide-rich rocks contain phlogopite, magnesian chlorite, and rutile, reflecting high /S2 during metamorphism. Metamorphic mineral assemblages along the Sedgwick pluton-Ellsworth Schist contact indicate contact metamorphism at pressures from 2.3 to 3.76 kbar (230-376 MPa) and at temperatures from 500-600°C. The magnesian metamorphic mineral assemblages result from combined effects of locally high /S]-/0] conditions during metamorphism and early hydrothermal alteration associated with formation of tile Zn-Pb-Cu deposits.